EXPORT DEVELOPMENT IN THE AGRO-INDUSTRIAL COMPLEX IN THE REPUBLIC OF UZBEKISTAN - Islamutdinova, Dina (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2025)
The article is an analysis of the export policy of the agro-industrial complex of Uzbekistan. The strengths and weaknesses of the export potential are analyzed, solutions are proposed to increase the competitiveness of agricultural products on the world market, taking into account the geographical location of the country and global trends. Government documents, statistical data, and scientific publications are used as sources of information.